Meningkatkan Minat dan Prestasi Belajar IPS Pokok Bahasan Penyimpangan Sosial dengan Pemberian Tugas Terstruktur Pada Siswa Kelas 8A SMP Negeri 2 Plosoklaten - Ainun, Nur (Jurnal Simki Pedagogia, 2020)
Every time they teach, teachers need to make teaching preparations in order to carry out part of the monthly plan and yearly plan. In the preparation it is already contained about, the purpose of teaching, the subject to be taught, teaching methods, lesson materials, teaching aids and evaluation techniques used. Therefore, every teacher must understand correctly about the purpose of teaching, specifically choosing and determining teaching methods according to the objectives to be achieved, how to choose, determine and use teaching aids, how to make tests and use them, and knowledge of evaluation tools. The purpose of this action research is to reveal the effect of giving structured assignments on learning outcomes of Social Knowledge and revealing structured task learning to interest in learning in grade 8A SMP Negeri 2 Plosoklaten. This study uses two cycles of action research. Each cycle consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this research is the students of Class 8A SMP Negeri 2 Plosoklaten . The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning achievement has increased from cycle I to cycle II, namely, cycle I (77%), cycle II (85%). The conclusion of this study is that the method of giving structured assignments can have a positive effect on student interest in learning at SMP Negeri 2 Plosoklaten and has an effect on learning achievement, and this learning model can be used as an alternative for learning Social Knowledge.